SAT0701 Pregnancy outcome is improved and similar to that of the general obstetric population in patients with rheumatoid arthritis who follow the "ideal clinical pathway" before and during pregnancy. (12th June 2018) - Andreoli, L.; Bortoluzzi, A.; Carrara, G.; Ramoni, V.; Padovan, M.; Govoni, M.; Tincani, A.; Scirè, C.A.
Abstract : Background: With the therapeutic advances of the last decades yielding to stable disease remission in the majority of patients, the goal of a successful pregnancy appears to be attainable for women affected by Rheumatoid Artrhitis (RA). However, individual risk stratification and measures to minimise it (e.g. withdrawal and wash-out of teratogenic drugs) are essential for the management of pregnancy in RA.( 1 Objectives: This analysis aims to evaluate the adherence to a reference clinical pathway of diagnostic, pharmacological and follow-up management in women with RA, and the influence of the adherence to this pathway on the outcome of pregnancy. Methods: Data were extracted from the Lombardy Region's (Italy) health databases for the period between 2004–2013. Patients with RA were identified through the chronic disease certification by rheumatologist (ICD9-CM code 714.0). Among these, women between the ages of 18 and 51 were selected. Data of controls from general population were also extracted. Conception has been approximated from the date of delivery or abortion. Seven healthcare quality indicators have been constructed: 1) screening of blood chemistry tests, 2) pre-conception musculoskeletal imaging, 3) pre-pregnancy antiphospholipid antibody tests, 4) ANA test and anti-ENA (antiRo/SSA) test, 5) no exposure or wash-out from teratogenic drugs (MTX/LEF); 6) no exposure to biological drugs; 7) rheumatological follow-up in outpatient visits. These 7 indicators were then summarised in 3 pathway indicators: 1) diagnostic pathway, 2) therapeutic pathway, 3) follow-up. The pregnancy outcome was defined on the basis of the DRG of complicated birth or abortion. Subanalysis on abortion was also done. The relationship between quality indicators and outcome variables was analysed using logistic models crude and adjusted for age and comorbidities, and the results presented as odds ratios (OR) and 95% confidence intervals (95% CI). Results: 443 pregnancies of patients with RA were identified, with median age of 34 (IQR 31–37), median disease duration at conception of 3.8 years (IQR 1.83–6.19), 157 (35.4%) of which with unfavourable outcome pregnancy outcome, of which 115 pregnancy losses. The increase or decrease of risk for those who meet specific quality indicators and pathway indicators showed a better outcome for patients screened for autoantibodies and with no exposure or washout from MTX/LEF (Table). The comparisons of those who followed the ideal pathway or not compared to the general population showed a significant increase of risk only for patients not following the ideal pathway (Table). Conclusions: The optimal management of pregnancy (stratification of pre-conceptional obstetric risk, modulation of therapy) in women with RA is associated with a reduced risk of unfavourable pregnancy outcome, bringing back that risk to that expected for a general obstetric control population. Reference: [1] Götestam Skorpen C, et al. The EULAR points to consider for use of antirheumatic drugs before pregnancy, and during pregnancy and lactation. Ann Rheum Dis2016May;75(5):795–810. Disclosure of Interest: None declared